2001
DOI: 10.1007/s00775-001-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the insulin-mimetic behaviour of vanadium(IV, V) coordination compounds

Abstract: A representative set of vanadium(IV and V) compounds in varying coordination environments has been tested in the concentration range 1 to 10(-6) mM, using transformed mice fibroblasts (cell line SV 3T3), with respect to their short-term cell toxicity (up to 36 hours) and their ability to stimulate glucose uptake by cells. These insulin-mimetic tests have also been carried out with non-transformed human fibroblasts (cell line F26). The compounds under investigation comprise established insulin-mimetic species s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
185
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 0 publications
8
185
0
1
Order By: Relevance
“…The VO (dipic) used may have a lower cytotoxicity to Caco-2 cells (which are originally derived from a human colorectal adenocarcinoma and are developed into a suitable model for the evaluation of intestinal absorption of drugs). Of relevance here is the fact that the IC 50 values of these three vanadium-dipic complexes is similar to those obtained for bis(maltonato)oxovanadium(IV), vanadyl acetylacetonate, and other vanadium (IV, V) complexes [Yang , et al 2004, Rehder, et al 2002. It also seems reasonable to exclude the presence of ethanol solvate (some concentration as complex, i.e.…”
Section: Cell Viability Assaysupporting
confidence: 68%
“…The VO (dipic) used may have a lower cytotoxicity to Caco-2 cells (which are originally derived from a human colorectal adenocarcinoma and are developed into a suitable model for the evaluation of intestinal absorption of drugs). Of relevance here is the fact that the IC 50 values of these three vanadium-dipic complexes is similar to those obtained for bis(maltonato)oxovanadium(IV), vanadyl acetylacetonate, and other vanadium (IV, V) complexes [Yang , et al 2004, Rehder, et al 2002. It also seems reasonable to exclude the presence of ethanol solvate (some concentration as complex, i.e.…”
Section: Cell Viability Assaysupporting
confidence: 68%
“…Among the many vanadium compounds reported in the literature, emphasis is given to the bis(matolato)oxidovanadium(IV) (BMOV) [11,14,37] and the similar one bis(ethylmaltolato) oxidovanadium(IV) (BEOV) [25], the only vanadium compounds tested in clinical trials to date, but other compounds like bis(1,2-dimethyl-3-hydroxy-4-pyridinonato)oxidovanadium(IV), [VO(dmpp) 2 ] [31,33,[36][37][38][39][40][41], bis(picolinato)oxidovanadium(IV) [VO(pic) 2 ] [24,42,43] and bis(allixinato)oxidovanadium(IV) [18,44,45] have also attracted much interest due to the positive results which have been obtained through in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…The VO(dmpp) 2 compound has been extensively studied for a structural characterization [30,31] and to investigate its therapeutic properties using adequate cellular models [33,[37][38][39][40]. Recently, it was shown that it is able to restore normal glucose and lipid metabolism in an obese pre-diabetic animal model, the Zucker fatty rats [36].…”
Section: Introductionmentioning
confidence: 99%
“…6,[13][14][15][16] Studies have been carried out with simple salts and coordination complexes of vanadium in oxidation states III, IV, 6,13,14,16 and V. 6,15,16 In addition to the animal studies, a range of studies was also carried out in several cellular systems, which probed the activity of specific classes of vanadium compounds and how these compounds act. [17][18][19] In such biological studies, the nature of the active vanadium compound cannot readily be identified, and consideration of chemical and metabolic processing is difficult. 6,15,16 However, various approaches to address this problem have provided some further insight as to the biological activity of these compounds.…”
Section: Introductionmentioning
confidence: 99%